Bipolar Disorder and Parkinson's Disease: A 123I-Ioflupane Dopamine Transporter SPECT Study - Erro, Roberto; Landolfi, Annamaria; D'Agostino, Giulia; Pace, Leonardo; Picillo, Marina; Scarano, Massimo; Cuocolo, Alberto; Pappatá, Sabina; Vitale, Carmine; Pellecchia, Maria Teresa; Monteleone, Palmiero; Barone, Paolo (Frontiers in Neurology, 2021)
Objectives: Bipolar disorder (BD) has been suggested to be a risk factor for the development of Parkinson's disease (PD). Standard treatment of BD includes drugs that are known to induce drug-induced parkinsonism (DIP). Clinical differentiation between PD and DIP is crucial and might be aided by functional neuroimaging of the dopaminergic nigrostriatal pathway. Methods: Twenty consecutive BD patients with parkinsonism were clinically assessed and underwent 123I-ioflupane dopamine transporter single-photon emission computer tomography (SPECT). Imaging data of BD patients with pathological scans were further compared to a population of 40 de novo PD patients. Results: Four BD patients had abnormal scans, but their clinical features and cumulative exposure to both antipsychotic drugs and lithium were similar to those of BD patients with normal dopamine transporter imaging. BD patients with pathological scans had putaminal binding ratio and putamen-to-caudate ratios higher than those of PD patients despite a similar motor symptom burden. Conclusions: Up to 20% of BD patients with parkinsonism might have an underlying dopaminergic deficit, which would not be due to cumulative exposure to offending drugs and is ostensibly higher than expected in the general population. This supports the evidence that BD represents a risk factor for subsequent development of neurodegenerative parkinsonism, the nature of which needs to be elucidated.